Where the bodies are burried - Brookmyre, Christopher, 1968- (Abacus, 2012)
Detective Catherine McLeod recognises that the discovery of a dead drug-dealer in a back alley is merely a portent of further deaths to come.Elsewhere, aspiring actress Jasmine Sharp is reluctantly earning a crust working for her uncle Jim's private investigation business.When Jim goes missing, Jasmine has to investigate for real.